2008
DOI: 10.1111/j.1365-2133.2008.08708.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pigmentation induction by repeated ultraviolet exposures: dose, dose interval and ultraviolet spectrum dependence

Abstract: SummaryBackground-The dynamics of UV-induced melanogenesis have been well-characterized for single UV exposures. However, our knowledge of the effects of repeated UV exposures on the development of new pigmentation is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 21 publications
3
46
0
Order By: Relevance
“…This observation was not surprising because similar trends of L* values had previously been reported in the human skin repetitively irradiated with UV [29]. It is thought that both pigmentation and depigmentation processes, and both inflammatory and antiinflammatory processes might be implicated during the later episodes of UV exposure.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This observation was not surprising because similar trends of L* values had previously been reported in the human skin repetitively irradiated with UV [29]. It is thought that both pigmentation and depigmentation processes, and both inflammatory and antiinflammatory processes might be implicated during the later episodes of UV exposure.…”
Section: Discussionsupporting
confidence: 51%
“…Previously, the a* parameter or erythema index of the skin has been measured to monitor inflammatory erythema [29,30], and the skin thickness has been used as an indicator of inflammatory edema [31,32]. Thus, considering the changes of skin color and thickness as the indirect indices of inflammation, it is thought that PCA might mitigate the UVB-induced inflammatory responses through UVB-shielding effects.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects (listed in Table 1) from 2 independent studies (Miller et al , 2008; Wolber et al , 2008) were invited to return for reexamination >1 yr after their initial UV exposures. Areas previously irradiated were identified using photos taken at the time of initial exposure, considering surface features and in some cases, pigmented areas that still remained.…”
Section: Resultsmentioning
confidence: 99%
“…The skin of most individuals generates a significant tanning response when repetitively exposed to UV (Parrish et al , 1981; Miller et al , 2008). It was previously reported that different wavelengths of UV induce different levels of modulation of melanocyte-specific markers, presumably via different mechanisms (Schlenz et al , 2005).…”
Section: Discussionmentioning
confidence: 99%